2019
DOI: 10.3389/fphys.2019.00080
|View full text |Cite
|
Sign up to set email alerts
|

KLF4-Induced Connexin40 Expression Contributes to Arterial Endothelial Quiescence

Abstract: Shear stress, a blood flow-induced frictional force, is essential in the control of endothelial cell (EC) homeostasis. High laminar shear stress (HLSS), as observed in straight parts of arteries, assures a quiescent non-activated endothelium through the induction of Krüppel-like transcription factors (KLFs). Connexin40 (Cx40)-mediated gap junctional communication is known to contribute to a healthy endothelium by propagating anti-inflammatory signals between ECs, however, the molecular basis of the transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…First, we examined the status of HSPCs in connexin41.8 ( cx41.8 ) mutant embryos. This connexin has been previously described in zebrafish 32 , 33 and we recently reported that cx41.8 plays an important role on ECs proliferation 34 . In zebrafish embryos, cx41.8 is enriched in caudal ECs, as well as in HSPCs and macrophages, to a lesser extent, as scored by qPCR on sorted kdrl:GFP + , ikaros:GFP + , and mpeg1:GFP + cells (Fig.…”
Section: Resultsmentioning
confidence: 60%
“…First, we examined the status of HSPCs in connexin41.8 ( cx41.8 ) mutant embryos. This connexin has been previously described in zebrafish 32 , 33 and we recently reported that cx41.8 plays an important role on ECs proliferation 34 . In zebrafish embryos, cx41.8 is enriched in caudal ECs, as well as in HSPCs and macrophages, to a lesser extent, as scored by qPCR on sorted kdrl:GFP + , ikaros:GFP + , and mpeg1:GFP + cells (Fig.…”
Section: Resultsmentioning
confidence: 60%
“…Also induced by laminar sheer stress, KLF4 promotes anti-inflammatory, and anti-thrombotic gene expression (25)(26)(27). Further, KLF4 promotes endothelial quiescence throughout a vascular bed via modulating gap junctional proteins and through the maintenance of proper proteostasis (28,29). These mechanisms protect against age-associated vascular disease, atherosclerosis, and ischemic stroke.…”
Section: Klf2 and Klf4 Regulate Vascular Homeostasis And Diseasementioning
confidence: 99%
“…Targeting Cx40 in vivo reduces angiogenesis in the developing mouse retina (56) and inhibits tumor growth by reducing angiogenesis (57). In an unbiased transcriptomics approach, cell cycle progression was identified as an important downstream target of Cx40 under arterial level of wall shear stress (58), illustrating that the regulation of proliferation by Cx40 may well extend beyond capillary ECs. Moreover, zebrafish embryos knockout for the Cx40 orthologues Cx41.8 and Cx45.6 displayed faster intersegmental vessel growth and branching into the dorsal longitudinal anastomotic vessels, an effect that was associated with increased EC proliferation (58).…”
Section: Connexins In Angiogenesismentioning
confidence: 99%
“…In an unbiased transcriptomics approach, cell cycle progression was identified as an important downstream target of Cx40 under arterial level of wall shear stress (58), illustrating that the regulation of proliferation by Cx40 may well extend beyond capillary ECs. Moreover, zebrafish embryos knockout for the Cx40 orthologues Cx41.8 and Cx45.6 displayed faster intersegmental vessel growth and branching into the dorsal longitudinal anastomotic vessels, an effect that was associated with increased EC proliferation (58). This suggests that the close relation between Cx40 and EC proliferation in sprouting angiogenesis is probably well conserved during evolution.…”
Section: Connexins In Angiogenesismentioning
confidence: 99%